SEXIST LANGUAGE SHOWING GENDER STEREOTYPES AS DEPICTED IN EFL TEXTBOOKS - Noviantika Saraswati; Rebecca Sarah Ayu (Sanata Dharma University, Yogyakarta, 2021)
One of the most prominent ways to shape children and adolescents’ mindset is through learning formally at school. EFL textbooks have an important role for students to learn English, but they will also unconsciously learn about gender stereotypes. These gender stereotypes include the belief that women’s role is limited to being a housewife, a good mother to her children, and an obedient woman for her husband. For men, their role is more to the wider part of society, which includes being a breadwinner and more successful in career. The object of this study is BSE English textbooks from grade X-XII. This paper will analyse sexist languages shown in the EFL textbooks using Mills (1995) theory and gender stereotypes using Arliss’ (1991) theory. This research is considered as descriptive qualitative research. The result shows that there are three types of sexist languages: fragmentation, presupposition and inference, and generic nouns. The second research formulation indicates that there are three gender stereotypes, namely stereotypes on traits, roles, and behavior.